Development of IoTs-based instrument monitoring application for smart farming using solar panels as energy source - Yovanka Davincy Setiawan; Bryan Ghilchrist; Gerry Giovan; Mochammad Haldi Widianto (International Journal of Reconfigurable and Embedded Systems (IJRES), 2023)
Indonesia is currently carrying out an industrial revolution 4.0. This revolution discusses the application of technology in the industrial sector, one of which is the agricultural sector. In addition to discussing the application of technology, this revolution also supports the use of renewable energy sources and one of them is the application of solar energy. The application of technology in the agricultural sector is expected to help farmers in maintaining crops to reduce the possibility of crop failure. The existence of this statement makes researchers conduct research in the design and construction of systems with internet of things (IoT) technology and utilize solar energy sources as energy sources for the system. The IoT system will utilize the ATmega328P+ESP8266 RobotDyn microcontroller by utilizing the DHT22, MD0127, soil moisture sensor, and BH1750FVI sensors and sending data to Thingspeak by utilizing the internet network with HTTP communication protocols. The system can monitor ecological factors in gardens with a fairly good degree of accuracy and the utilization of solar energy can run the system properly.